2001
DOI: 10.1007/s004390100600
|View full text |Cite
|
Sign up to set email alerts
|

A frameshift mutation in exon 28 of the OPA1 gene explains the high prevalence of dominant optic atrophy in the Danish population: evidence for a founder effect

Abstract: Dominant optic atrophy (DOA) is a hereditary optic neuropathy characterised by decreased visual acuity, colour vision deficits, centro-coecal scotoma and optic nerve pallor. The gene OPA1, encoding a dynamin-related GTPase, has recently been identified within the genetic linkage interval for the major locus for DOA on chromosome 3q28 and shown to harbour genetic aberrations segregating with disease in DOA families. The prevalence of the disorder in Denmark is reported to be the highest of any geographical loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…It has been recently confirmed that OPA1 is involved in the biogenesis and maintenance of mitochondria in mice [Misaka et al, 2002], as well as in humans [Olichon et al, 2002]. Sixty-nine OPA1 gene mutations, mainly family-specific, have been described so far, and the results of these studies support the hypothesis that haploinsufficiency with null mutations and the functional loss of one allele may represent a major mechanism of ADOA [Pesch et al, 2001;Thiselton et al, 2001;Toomes et al, 2001;Delettre et al, 2002;Marchbank et al, 2002]. We report here 14 new OPA1 mutations found in 44 patients with a family history of optic atrophy.…”
Section: Introductionmentioning
confidence: 75%
“…It has been recently confirmed that OPA1 is involved in the biogenesis and maintenance of mitochondria in mice [Misaka et al, 2002], as well as in humans [Olichon et al, 2002]. Sixty-nine OPA1 gene mutations, mainly family-specific, have been described so far, and the results of these studies support the hypothesis that haploinsufficiency with null mutations and the functional loss of one allele may represent a major mechanism of ADOA [Pesch et al, 2001;Thiselton et al, 2001;Toomes et al, 2001;Delettre et al, 2002;Marchbank et al, 2002]. We report here 14 new OPA1 mutations found in 44 patients with a family history of optic atrophy.…”
Section: Introductionmentioning
confidence: 75%
“…The gene encoding for Opa1 is composed of 30 exons, and at least eight mRNA isoforms arising from alternative splicing and with tissue-specific expression have been identified (Delettre et al, 2001). A total of 83 family-specific mutations have been associated with ADOA so far, and their number seems to be growing (Alexander et al, 2000;Delettre et al, 2000Delettre et al, , 2001Delettre et al, , 2002Pesch et al, 2001;Thiselton et al, 2001Thiselton et al, , 2002Toomes et al, 2001;Marchbank et al, 2002;Shimizu et al, 2002;Amati-Bonneau et al, 2005;Ferre et al, 2005). About half of the mutations associated with the disease are located within the GTPase domain, suggesting that pathogenesis is related to loss of function of the protein and haploinsufficiency in patients with mutation on a single allele (Ferre et al, 2005).…”
Section: Fusionmentioning
confidence: 99%
“…41 There is a wide spectrum of mutations throughout the gene, with over 70 reported to date. 37,38,[41][42][43][44][45][46] There is a concentration of mutations in the GTPase and dynamin central region (coded for by exons 8 to 28), but to date no mutations have been found in exons 4, 4b, and 5b, which are alternately spliced. Since the majority of mutations result in protein truncation, and most mutations probably represent null alleles, dominant inheritance of the disease may result from haploinsufficiency of OPA1.…”
Section: The Opa1 Genementioning
confidence: 99%